Formation and Development of State Migration Policy - JUSSUPOV, Murat; BOZHKARAULY, Altai; RUSTEMBEKOVA, Dinara (Journal of Advanced Research in Law and Economics, 2018)
The article discusses the main national documents in the field of state regulation of migration processes in the Republic of Kazakhstan. A number of regulatory legal acts on the regulation of migration processes were studied, such as: the Law of the Republic of Kazakhstan ‘On Migration of the Population’, the Concept of the Migration Policy of the Republic of Kazakhstan.